Development of a Rat Model of Intra-Amniotic Inflammation via Ultrasound-Guided Administration of a Triggering Agent in the Gestational Sac to Enable Analysis of Individual Amniotic Fluid Samples - Jaroslav Stranik; Marian Kacerovsky; Marian Kacerovsky; Martin Sterba; Ctirad Andrys; Cilia Abad; Frantisek Staud; Stanislav Micuda; Ondrej Soucek; Bo Jacobsson; Bo Jacobsson; Bo Jacobsson; et al. (Frontiers Media S.A., 2022)
Objectives: To develop a rat model of intra-amniotic inflammation, characterized by the concentration of interleukin-6 in the amniotic fluid, induced by an ultrasound-guided transabdominal administration of lipopolysaccharide into individual gestational sacs.Methods: An ultrasound-guided transabdominal intra-amniotic administration of lipopolysaccharide or phosphate-buffered saline (PBS) as control was performed in rats on embryonic day 18. Only accessible gestational sacs with precise recording of their positions were injected. Twenty-four hours later, individual amniotic fluid samples were collected from the gestational sacs of laparotomized animals. The gestational sacs were divided into four subgroups: (i) with lipopolysaccharide: injected gestational sacs from rats undergoing lipopolysaccharide administration; (ii) without lipopolysaccharide: non-injected gestational sacs from rats undergoing lipopolysaccharide administration; (iii) with PBS: injected gestational sacs from rats undergoing PBS administration; and (iv) without PBS: non-injected gestational sacs from rats undergoing PBS administration. The concentration of interleukin-6 in individual amniotic fluid samples was assessed using ELISA.Results: In the group of five animals receiving lipopolysaccharide, 24 (33%) and 48 (77%) gestational sacs were and were not injected, respectively. The amniotic fluid was obtained from 21 (88%) injected and 46 (95%) non-injected sacs. In the control group of five animals receiving phosphate-buffered saline, 28 (35%) and 52 (75%) gestational sacs were and were not injected, respectively. The amniotic fluid was obtained from 18 (64%) injected and 50 (96%) non-injected sacs. No labor occurred, and only one fetal death was observed in a gestational sac injected with lipopolysaccharide. Differences in concentrations of interleukin-6 in the amniotic fluid were found among the subgroups of the gestational sacs (with lipopolysaccharide: median 762 pg/ml; without lipopolysaccharide: median 35.6 pg/ml; with PBS: median 35.6 pg/ml; and without PBS: median 35.6 pg/ml; p < 0.0001). Concentrations of interleukin-6 in the amniotic fluid from the gestational sacs with lipopolysaccharide were significantly higher than those in the three remaining subgroups (p < 0.0001). No differences in concentrations of interleukin-6 in the amniotic fluid were identified between the three remaining subgroups.Conclusion: The ultrasound-guided transabdominal intra-amniotic administration of lipopolysaccharide with a subsequent collection and analysis of amniotic fluid samples is feasible in rats. The intra-amniotic administration of lipopolysaccharide led to the development of intra-amniotic inflammation without leading to fetal mortality or induction of labor.